2019
DOI: 10.1155/2019/5015824
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Preparation Combined Therapy May Improve Chemotherapy Efficacy: A Systematic Review and Meta-Analysis

Abstract: Background. Whether traditional Chinese medicine preparation combined therapy can improve the efficacy of chemotherapy is controversial. This meta-analysis evaluates the efficacy of traditional Chinese medicine preparation combined with chemotherapy. Method. Three databases were searched from inception through August 2018. Eligible randomized controlled trials (RCTs) involving the combined treatment of chemotherapy and traditional Chinese medicine preparation compared to chemotherapy alone for treating cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Zou and colleagues [15] found that PHY906 exerts a protective effect in IBD by down-regulated production of pro-inflammatory cytokines and suppression of the NF-κB signaling pathway. Several clinical studies have demonstrated that TCM, as an alternative treatment for cancer, can reduce the incidence of bone marrow suppression and gastrointestinal reactions in chemotherapy [16][17][18]. In addition to mitigate the side effects of chemotherapy, the combination of chemotherapy and TCM also improves the chemosensitivity of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Zou and colleagues [15] found that PHY906 exerts a protective effect in IBD by down-regulated production of pro-inflammatory cytokines and suppression of the NF-κB signaling pathway. Several clinical studies have demonstrated that TCM, as an alternative treatment for cancer, can reduce the incidence of bone marrow suppression and gastrointestinal reactions in chemotherapy [16][17][18]. In addition to mitigate the side effects of chemotherapy, the combination of chemotherapy and TCM also improves the chemosensitivity of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The conclusions drawn from most of these studies suggest that, for cancer patients, TCM can be useful and effective, helping to control the disease, prolonging survival time, alleviating side effects of chemotherapy and radiotherapy, and improving the quality of life [ 95 ]. One systematic review summarized that traditional Chinese medicine preparations, combined with chemotherapy, may improve the objective response rates and disease control rates more than chemotherapy alone [ 96 ]. Throughout these years, pharmacognosists, pharmacologists, and biochemists are anticipating more and more scientific evidence on the efficacies of medicinal herbs, to be gained through modern pharmacological research approaches.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether using a traditional herbal formula as an adjuvant therapy to conventional drugs can potentiate the efficacy of chemotherapy and reduce adverse effects is controversial. A recent systematic review raised questions regarding the efficacy of herbal decoctions combined with conventional chemotherapeutic agents [ 79 ]. However, combinational therapeutic strategies to enhance anticancer properties and decrease side effects have received attention.…”
Section: Possibility Of the Combined Use Of O Japonica mentioning
confidence: 99%